Efektivitas Promosi Kesehatan dalam Meningkatkan Perilaku Masyarakat Memberantas Sarang Nyamuk di Yogyakarta - Sujono Riyadi; Ferianto Ferianto (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
Dengue hemorrhagic fever is a disease that requires prompt and appropriate treatment so that the sufferer does not experience a more severe condition. This disease is spread in almost all parts of Indonesia and has become a public health problem because many areas are endemic. The purpose of this study was to compare and determine the effect of providing health promotion with the lecture and small group discussion method on community behavior changes in eradicating mosquito nests. The design of this research was a survey method with a quasi-experimental design. This study was conducted in Gunungkidul District from May to July 2020. The number of samples was 400 persons, a total of 200 subjects were given health promotion interventions with the lecture method and 200 subjects were given a small group discussion method. The presence of mosquito larvae was checked before and after the intervention. The Mann-Whitney test was used when the data are not normally distributed. The result of this study show that health promotion with the small group discussion method is more effective than the lecture method on community behavior in eradicating mosquito nests.